Amplification of Coccidioidal DNA in Clinical Specimens by PCR - Johnson, Suzanne M. (American Society for Microbiology, 2004)
Coccidioides DNA was amplified from serum by a PCR using coccidioid-specific primers. A 239-bp product was visualized when 10 fg of exogenous coccidioidal DNA was subjected to amplification. This product was demonstrated in some human and mouse sera prior to the detection of coccidioidal antibodies.